Application of strut-and-tie models for assessing RC half-joints not complying with current code specifications - Kotsovou, Gregoria; Vougioukas, Emmanouil; Cotsovos, Demetrios M. (Acta Polytechnica, 2022)
The work described is concerned with an investigation of the effectiveness of the use of strut-and-tie models for the structural assessment of half joints. Such elements form a part of many existing bridges which, although not complying with current code specifications, have not as yet displayed any significant signs of distress in spite of the increase in traffic volume and loads over the years. The work is based on a comparative study of the predicted and experimentally established values of load-carrying capacity and location and causes of failure of half-jointed beams with reinforcement layouts that replicate those found in structures designed in accordance with previous code specifications. The results obtained show significant shortcomings of the assessment method as this is found not only to underestimate load-carrying capacity by a margin ranging between 40 % and 65 %, but also to often fail to identify the location and causes of failure. Therefore, there is a need for an alternative assessment method that will be based on concepts capable of both providing a realistic description of structural-concrete behaviour and identifying the causes of failure leading to the loss of load-carrying capacity.